INTEGRATED MODELS OF FORECASTING RELIABILITY OF DECISION MAKING OF THE SYSTEM OF DIAGNOSTICS OF THE TECHNICAL CONDITION OF BUILDINGS - Терентьєв, Олександр; Горбатюк, Євгеній; Тисленко, Олександр; Зубрій, Іван (SWorldJournal, 2024)
The conducted research allows to propose an approach to solving the problem of choosing a model describing the change in the dynamics of the measured data due to the ageing and deterioration of structures, allow to choose the degree of complexity of the